THE EFFECT OF GRATED RED GINGER COMPRESS ON REDUCING RHEUMATHOID ARTHRITIS PAIN IN THE ELDERL: LITERATURE REVIEW - Cicilia Aditya Melinda; Rahmaya Nova H; Tophan Heri (Sekolah Tinggi Pariwisata Mataram, 2023)
Red ginger grated poultice provides a non-pharmacological effect that reduces pain. The efficacy of red ginger is very diverse, one of which is to relieve joint pain in the elderly who suffer from rheumatoid arthritis. A poultice of grated red ginger can relieve pain in rheumatoid arthritis because of the water and non-volatile oil in ginger. The purpose of this study was to analyze the effect of hot red ginger poultice in relieving pain in the elderly with rheumatoid arthritis, based on a literature review. The type of research used in this study is an analytic type based on a literature review. The literature search was based on advanced research journals. The results of a study of 11 peer- reviewed journals found the effectiveness of red ginger poultice in reducing rheumatoid arthritis pain in the elderly.